The empirical evidence of digital trends in more disadvantaged European Union regions in terms of income and population density - Garashchuk, Anna; Isla-Castillo, Fernando; Podadera-Rivera, Pablo (Wiley, 2024)
Remote rural and postindustrial regions are much morevulnerable to population drain in comparison with indus-trialized centers and capitals, due to obvious reasons suchas meager job opportunities, difficulties in accessing publicservices in education, healthcare and transport, housing,entertainment, lack of integration with other territoriesand, finally, less advanced levels of digitalization. Thisrepresents an open challenge for the European Unionwithin the framework of its Cohesion Policy. This paperanalyzes the impact of digital trends, represented by thepercentage of the population with access to internet andbroadband and the percentage of individuals who buygoods and internet services (percentages provided byEurostat) in less populated EU NUTS2 regions with lowerincome, on the crude population growth rate composed ofnatural changes in population and migratory flows and onthe unemployment rate by applying panel data analysis. Ithas been possible to confirm that digitalization has a pos-itive impact on natural changes in population in EU regionswith lower economic development. On the contrary, theunemployment rate does not affect natural changes inpopulation, but it does have a negative impact on migratory
Keywords: Población rural; Dinámica de población; Migración; Economía aplicada; Depopulation; Digitalization; EU regions; European Union; Paneldata analysis